History of the Atchison, Topeka and Santa Fe Railway - Bryant Jr., Keith L. (Bison Books, 2020)
This new edition of the first comprehensive history of the financing, construction, growth, and management of the Atchison, Topeka and Santa Fe Railway includes nearly twenty-five more years of history..